Cerebral Collaterals and Collateral Therapeutics for Acute Ischemic Stroke. (April 2015) - Winship, Ian R.
Abstract Cerebral collaterals are vascular redundancies in the cerebral circulation that can partially maintain blood flow to ischemic tissue when primary conduits are blocked. After occlusion of a cerebral artery, anastomoses connecting the distal segments of the MCA with distal branches of the ACA and PCA (known as leptomeningeal or pial collaterals) allow for partially maintained blood flow in the ischemic penumbra and delay or prevent cell death. However, collateral circulation varies dramatically between individuals, and collateral extent is significant predictor of stroke severity and recanalization rate. Collateral therapeutics attempt to harness these vascular redundancies by enhancing blood flow through pial collaterals to reduce ischemia and brain damage after cerebral arterial occlusion. While therapies to enhance collateral flow remain relatively nascent neuroprotective strategies, experimental therapies including inhaled NO, transient suprarenal aortic occlusion, and electrical stimulation of the parasympathetic sphenopalatine ganglion show promise as collateral therapeutics with the potential to improve treatment of acute ischemic stroke.